Levels of Soluble CD14 and Tumor Necrosis Factor Receptors 1 and 2 May Be Predictive of Death in Severe Coronavirus Disease 2019. (29th November 2020) - Bowman, Emily R; Cameron, Cheryl M Ainslie; Avery, Ann; Gabriel, Janelle; Kettelhut, Aaren; Hecker, Michelle; Sontich, Claudia Ute; Tamilselvan, Banumathi; Nichols, Carmen N; Richardson, Brian; Cartwright, Michael; Funderburg, Nicholas T; et al.
Abstract: People infected with severe acute respiratory syndrome coronavirus 2 display a wide range of illness, from asymptomatic infection to severe respiratory distress resulting in death. We measured serum biomarkers in uninfected individuals and in individuals with mild, moderate, or critical coronavirus disease 2019 (COVID-19) disease. Levels of monocyte activation (soluble CD14 and fatty acid–binding protein 4) and inflammation (tumor necrosis factor receptors 1 and 2 [TNFR1 and TNFR2]) were increased in COVID-19 individuals, regardless of disease severity. Among patients with critical disease, individuals who recovered from COVID-19 had lower levels of TNFR1 and TNFR2 at hospital admission compared to these levels in patients with critical disease who ultimately died. Abstract : Individuals infected with severe acute respiratory syndrome coronavirus 2 display increased inflammation and monocyte activation, regardless of disease severity. Higher levels of tumor necrosis factor receptors 1 and 2 were associated with death in patients with severe coronavirus disease 2019.